Discovery and structure–activity relationship of plastoquinone analogs as anticancer agents against chronic myelogenous leukemia cells. Issue 12 (11th October 2019) - Ciftci, Halil I.; Bayrak, Nilüfer; Yıldırım, Hatice; Yıldız, Mahmut; Radwan, Mohamed O.; Otsuka, Masami; Fujita, Mikako; Tuyun, Amaç F.
Abstract: Two series of amino‐1, 4‐benzoquinones (AQ1–18 ) based on the structural analogs of plastoquinones were synthesized and the structure–activity relationship against chronic myelogenous leukemia activity was examined. All of the synthesized compounds were tested for their cytotoxic effects on different leukemic cell lines. Of interest, AQ15 exhibited a better selectivity than the reference drug imatinib on cancer cells. Owing to this, AQ15 was selected for a further apoptosis/necrosis evaluation where AQ15 ‐treated K562 cells demonstrated similar apoptotic effects like imatinib‐treated cells at their IC50 values. The inhibitory effects of AQ15 and the other three compounds with various activities against eight tyrosine kinases, including ABL1, were investigated. AQ15 showed weak activity against ABL1, and a correlation was observed between the anti‐K562 and anti‐ABL1 activities. The binding mode of AQ15 into the ATP binding pocket of ABL1 kinase was predicted in silico, showing the formation of some key interactions. In addition, AQ15 was shown to suppress the downstream signaling of BCR‐ABL in K562 cells. Finally, AQ15 obviously cleaved DNA in the presence of an iron(II) complex system, indicating that this can be the major mechanism of its antiproliferative action, whereas the mild inhibition of ABL kinase is just in‐part mechanism of its overall outstanding cellular activity. Abstract : Two series of aminobenzoquinones were synthesized and evaluated for their anticancer activity. AQ11, AQ12, and AQ15 showed better antiproliferative activity than the clinically prevalent anticancer drug imatinib against the human CML cell line K562. The inhibitory effects of AQ15 were investigated against eight tyrosine kinases including ABL1, indicating that AQ15 has a unique anti‐CML activity with mechanisms including tyrosine kinase inhibition and DNA cleavage.